Ecological niche modelling of Gargaphia decoris (Heteroptera), a biological control agent of the invasive tree Solanum mauritianum (Solanales: Solanaceae) - Minghetti, Eugenia (2020)
BACKGROUND: The South American tree Solanum mauritianum Scopoli (Solanaceae) is a problematic invasive plant in numerous tropical, subtropical and temperate regions around the globe. Because conventional management approaches are not cost-effective, biological control provides an alternative approach. Gargaphia decoris Drake (Tingidae) is currently used as a biological control agent in South Africa and New Zealand. Considering the importance of climate in the establishment and success of a biological control agent, this study used ecological niche models (ENM) to identify areas where S. mauritianum is a problematic invader and where suitable conditions exist for G. decoris. Additionally, the climate niche dynamics of G. decoris were investigated and ENMs projected worldwide for the year 2050 were built. RESULTS: Our results indicate that most of the countries where S. mauritianum is problematic have suitable climatic conditions for G. decoris, and that the species can survive in climates with temperatures lower than those in its native range. For future climates, ENMs predict wider regions with favourable climatic conditions for G. decoris. CONCLUSION: Considering the results of this study, the prospects of using G. decoris as a biological control agent are good under current and future climates. Introduction of this agent could be considered in affected countries where it has not been released. © 2019 Society of Chemical Industry.